The Souls of Animals in Christianity and Mahāyāna Buddhism - Shin, Junhyoung (Buddhist Christian studies, 2019)
Both Christians and Buddhists have largely assumed that Buddhism, not Christianity, values the lives of animals and believes in the continuous existence of the animal soul or spirit after death. This article, however, argues otherwise, by examining Christian scriptures and visual traditions from the medieval to the early modern periods. Though Christianity has never asserted the immortality of animal souls as dogma, Christians appear to have lived with a constant awareness that not only humans but also animals can recognize and even serve the divine will. Furthermore, some Christians have also suspected that animal souls might join them in heaven at the end of time. First, I briefly review the Buddhist teachings and imagery on animal souls, which are believed to have equal status with human souls. I then turn to the Judaic scriptures that value animal souls and question the validity of animal sacrifice. Finally, I discuss the Christian iconographies of the Nativity, St. Blaise, and St. Francis preaching to the birds, and argue that a serious concern for animal life has always been present in medieval and early modern Christianity.